Pengaruh Pembelajaran IPA dengan Model Kooperatif Tipe Group Investigation Berbantuan Lembar Kerja Siswa Terhadap Pemahaman Konsep dan Keterampilan Proses Sains pada Siswa Kelas V - Nasirun; Irwan Koto; Endang Widi Winarni (UNIB Press, 2024)
The aim of this research is to analyze the eﬀect of science learning with cooperative type model Group Investigation assisted by Student Worksheets on understanding concepts and science process skills in ﬁfth grade students. This research is a quantitative research. The method used is Quasi Experimental Design (pseudo-experimental research). The research design used is Nonequivalent Control Group Design. The research samples were 25 students in class V at SDN Trans Pendingan as an experimental class and 24 students in class V at SDN Anyar as a control class. The data collection technique is done by testing pretest and posttest. The instruments given were 20 questions consisting of aspects of understanding concepts totaling 15 multiple choice questions and aspects of science process skills totaling 5 Essay questions. The results showed that the average value of the concept understanding variable between the experimental class and the control class had an increase diﬀerence of 20.72%. While the average value of the science process skills variable has an increase diﬀerence of 4.63%. So it can be concluded that there is a signiﬁcant inﬂuence on science learning with the type cooperative model Group Investigation assisted by Student Worksheets on understanding concepts and science process skills in ﬁfth grade students.